Animal‐mediated seed dispersal in India: Implications for conservation of India's biodiversity. (13th June 2021) - Sengupta, Asmita
Abstract: Effective seed dispersal is critical for forest regeneration and recruitment as well as the restoration of degraded lands. Most tropical tree species depend on frugivorous animals to disperse their seeds; frugivore‐mediated seed dispersal is thus crucial for biodiversity conservation in megadiverse tropical systems such as India. The fauna in India are increasingly threatened due to anthropogenic interventions such as deforestation and hunting. Thus, it is imperative to have an understanding of plant–frugivore interactions across the country to curb further biodiversity loss by ensuring the maintenance of these ecological processes. In this paper, I reviewed the literature on seed dispersal by animals in India to identify important groups that disperse many plant species and/or are the only recorded dispersers of certain plant species. Hornbills, bulbuls, bears, cattle, deer, civets, elephants, macaques, nilgais, Old World fruit bats, and wild pigs meet these criteria; overall 18 species were included in this list. Six of these species are currently "Threatened" on the IUCN Red List and their loss can lead to limited dispersal for at least 86 plant species. I suggest ensuring the protection of the important seed dispersers identified in this paper, irrespective of their conservation status, to prevent further biodiversity loss. The review reveals that plant–animal interactions in India are understudied and a major knowledge gap exists with regard to seed dispersal networks within the country. Abstract : In this paper, I reviewed the literature on seed dispersal by animals in India to identify important groups that disperse many plant species and/or are the only recorded dispersers of certain plant species. Hornbills, bulbuls, bears, cattle, deer, civets, elephants, macaques, nilgais, Old World fruit bats and wild pigs meet these criteria; overall 18 species were included in this list. Six of these species are currently 'Threatened' on the IUCN Red List and their loss can lead to limited dispersal for at least 86 plant species. Photo credits: Kulpat Saralamba (Hornbill, Bear, Civet, Elephant); Rhett A. Butler, Mongabay.com (Bat, Bulbul, Deer); Suresh Roy (Macaque).